1949
DOI: 10.1063/1.1747345
|View full text |Cite
|
Sign up to set email alerts
|

The Formula of Uranyl Ion

Abstract: The exchange of oxygen between uranyl ion and water was studied using oxygen 18 as a tracer. The results showed that the formula of uranyl ion in dilute hydrochloric acid solution is UO2++, neglecting any anion complexing, as distinguished from U(OH)4++, unless in U(OH)4++ two of the oxygen atoms are much more weakly bonded than the other two. The UO2++ ion is covalently bonded in dilute hydrochloric acid solution as well as in crystalline uranyl chloride. The Raman spectrum of uranyl perchlorate was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

1956
1956
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 9 publications
1
46
0
1
Order By: Relevance
“…Facile OH exchange as compared with O yl exchange is in accord with the rationale presented by Crandall that a covalent U−O yl bond should be more resistant to disruption than an ionic U−OH bond. 1 The O yl exchange efficiency for UO 2 + was much greater than for NpO 2 + and PuO 2 + . DFT results for UO 2 + , NpO 2 + , and PuO 2 + indicate a substantially higher energy transition state for the latter two, in accord with the observations.…”
Section: ■ Conclusionmentioning
confidence: 98%
“…Facile OH exchange as compared with O yl exchange is in accord with the rationale presented by Crandall that a covalent U−O yl bond should be more resistant to disruption than an ionic U−OH bond. 1 The O yl exchange efficiency for UO 2 + was much greater than for NpO 2 + and PuO 2 + . DFT results for UO 2 + , NpO 2 + , and PuO 2 + indicate a substantially higher energy transition state for the latter two, in accord with the observations.…”
Section: ■ Conclusionmentioning
confidence: 98%
“…42 These equatorial aqua ligands are labile and interchange with the aqueous media, whereas the two oxygen centers of uranyl are inert with respect to substitution. 96,97 Quite a few theoretical studies 7-9,15-18,53 computed the effects of hydration on UO 2 2+ considering 4, 5, and 6 water molecules in the equatorial plane. On the basis of solvation energetics, several authors identified the pentacoordinated complex as energetically preferred.…”
Section: Chloro Complexes [Ano 2 CL 4 ] 2- [Uo 2 Cl 4 ] 2-mentioning
confidence: 99%
“…22 They obtained IR spectra for neutral uranyl hexafluoroacetylacetonate (hfac) adducts with additional basic ligands. The bare 4 complex, which can simplistically be formulated as UO 2 2+ (hfac -) 2 , exhibited a ν 3 of 958 cm -1 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The infrared (IR) active asymmetric v 3 stretching mode of uranyl has been studied extensively in both condensed and gas phases, with a focus on the effect of ligation on the frequency. In aqueous solution the hydrated uranyl ν 3 frequency is close to 963 cm -1 .…”
Section: Introductionmentioning
confidence: 99%